The Oxidative Cyclization of Ketone Carbohydrazones and 4-Substituted Semicarbazones. Thermal Decomposition of 5,5-Diaryl-2-Phenylimino-△^3 -1,3,4-Oxadiazolines - West, Paul Ronald (My University, 1967)
The reaction of lead tetra-acetate with ketone carbohydrazones and 4-substituted semicarbazones gave a series of 2-(substituted imino)-△^3-1,3,4-oxadiazolines. Spectroscopic and chemical evidence is presented to establish the proposed structure, and the scope of the reaction is described. The thermolysis of the 5,5-diaryl-2-phenylimino-△^3-1,3,4-oxadiazolines was studied in chlorobenzene solution. The results of kinetic experiments (gas evolution and infra-red) are reported, and the mechanism of the decomposition is discussed. A survey of the literature pertaining to related lead tetra-acetate oxidations, and to decomposition of cyclic azo compounds is presented.
Keywords: oxidative, cyclization, ketone, carbohydrazones, semicarbazones, decomposition, reaction